Traditions and current trends of china’s vocal and choir school development - Lin, Khay (Pedagogy of Higher and Secondary Education, 2006)
The article reveals ancient traditions and significance of singing activities in China. The modem tendencies оf development of Chinese vocal-choral schools are characterized as well.